Australia Under Construction Nation-building past, present and future - Butcher, John (ANU Press, 2008)
The Australian nation is a work in progress. So conclude the authors whose views are represented in this most recent offering in the ANZSOG monograph series, Australia Under Construction: Nation-building past, present and future. From its beginnings as a settler society through to present day concerns about 'broadbanding the nation', the nation-building narrative has resonated with Australians. The very idea of nation-building has both excited the popular imagination about what we might achieve as a society and a nation, and has occasioned despair about missed opportunities. The eleven authors contributing to this monograph reflect on these, and other themes from a variety of perspectives. They challenge our understanding of the term 'nation-building', reflect on its contemporary relevance as a framework for public policy and even re-appraise the contribution of past 'iconic' nation-building endeavours. To this subject the authors bring intelligence, wit and a healthy disdain for sacred cows. A stimulating read for anyone interested in the history, challenges and prospects of nation-building in Australia.